2017
DOI: 10.1002/jssc.201600813
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis combined with chromatographic fingerprint and antioxidant activities for the comprehensive evaluation of Compound Danshen Tablets

Abstract: The composition of traditional Chinese medicine is extremely complex, so it is difficult to ensure quality consistency. We took Compound Danshen Tablets as the object of the study, by using high-performance liquid chromatography to establish multiwavelength fusion fingerprints. Characteristic fingerprints of 30 batches of samples were generated at four wavelengths and evaluated by systematic quantified fingerprint method. An on-line antioxidant determination method was used for the determination of the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Oxidation is an important process for the energy productive of many biological organs [50]. Studies have shown that cancer, inflammation, blood diseases, and other diseases are closely related to oxidative free radicals, and excessive free radicals in the human body will lead to aging [51][52][53].…”
Section: Antioxidant Activities Of 21 Batches Of Saffronmentioning
confidence: 99%
“…Oxidation is an important process for the energy productive of many biological organs [50]. Studies have shown that cancer, inflammation, blood diseases, and other diseases are closely related to oxidative free radicals, and excessive free radicals in the human body will lead to aging [51][52][53].…”
Section: Antioxidant Activities Of 21 Batches Of Saffronmentioning
confidence: 99%
“…Recently, the chromatographic fingerprint technique has been introduced as a tool to evaluate the quality of herbal samples or their derived products [10][11][12][13]. This technique has been accepted by the WHO and European Medicines Agency (EMEA) as a strategy for the quality assessment of herbal medicines [14] and gained more and more attention, because it emphases on the characterization of the complete sample composition.…”
Section: Introductionmentioning
confidence: 99%
“…The chromatographic fingerprinting approach has been accepted by the World Health Organization (WHO) to evaluate and QC of various traditional Chinese medicine (TCM) in recent years . When the fingerprint method was adopted by the official pharmacopoeia, it became common practice to use a developed fingerprint method with fixed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The chromatographic fingerprinting approach has been accepted by the World Health Organization (WHO) to evaluate and QC of various traditional Chinese medicine (TCM) in recent years [1,2]. When the fingerprint method was adopted by the official pharmacopoeia, it became common practice Article Related Abbreviations: AQbD, analytical quality-by-design; CMA, critical method attribute; CMP, critical method parameter; DAD, diode-array detector; QbD, quality by design; TCM, traditional Chinese medicine to use a developed fingerprint method with fixed conditions.…”
Section: Introductionmentioning
confidence: 99%